ANALYSIS OF DIFFERENTIATED ASSESSMENT BASED ON THE EMANCIPATED CURRICULUM IN 8TH-GRADE JUNIOR HIGH SCHOOL STUDENTS - Made Gitananda Pramudya Candra Wardhani; Budiarta, Luh Gd Rahayu; Utami, Ida Ayu Made Istri (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The Emancipated Curriculum represents an innovative strategy for teaching and learning in the classroom. Differentiated assessment plays a crucial role in evaluating student performance based on individual learning styles and needs. The research focused on the analysis of differentiated assessment implemented in eighth-grade junior high school at one of the junior high schools in Singaraja. Data collection methods included observation of teaching activities, teacher interviews, and student questionnaires regarding learning methods and student learning styles. The researcher also conducted a questionnaire to the students which consisted of 6 yes/no questions and 12 multiple-choice questions. Results showed varied learning styles among students, with a majority favoring kinesthetic and visual learning styles, whereas students in 8th grade preferred a visual learning style. The results of the study show that differentiated assessment has never been implemented in schools even though the results of student questionnaires show that students have different learning styles. Additionally, the differentiated assessment is essential for supporting diverse student needs in the Emancipated Curriculum. Further research and implementation of differentiated assessments are needed to enhance students' learning outcomes in junior schools.